Flops Laboratory Practice Facility towards Cadet’s Flight Plan Navigation Course Performance - Ilya Himmah, Kuny; Maharani Sukma, m; Dewi Kusumayati, Lusiana (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
One of the laboratories to support learning activities in the Air Transportation Management Study program at the Surabaya Aviation Polytechnic is the Flops Laboratory. The use of laboratories that are less than optimal due to the incompleteness of the available practical facilities can affect the academic abilities of cadets. This study has the objectives of (1) the current condition of the Flops Laboratory practice facilities (2) The value of the academic ability of Air Transportation Management cadets in the Aviation Navigation Planning Course to know (3) to determine the effect of flops laboratory practice facilities on the academic abilities of cadets in planning courses flight navigation reviewed from the results of the final exam assessment. This research is quantitative. The population in this study were cadets of Air Transportation Management batches VI and VII with observation data collection methods, questionnaires and documentation and interviews. The results of this study is (1) The condition of the Flops Laboratory practice facilities was still not in accordance with the Flops Laboratory standards and the actual Flops room (2) The value of academic ability for Cadets in the Flight Navigation Planning course has a sufficient category of 90% in the range 70 - 79 (3) The result of T test it has a significant value of 0.000 <0.005 which means there is an influence from the Flops Laboratory practice facility on Cadets Academic Ability Flight Navigation Planning Course. Based on the results of the simple regression test, a result of 0.622 or equal to 62.2% was obtained.